Analysis of the characteristics of mouthguards that affect isokinetic muscular ability and anaerobic power - Jung, Jae-Kwang (The Korean Academy of Prosthodontics, 2013)
PURPOSE: The purpose of this study was to estimate the effects of occlusal stability to identify action mechanisms of mouthguards, known to have a modulatory effect on limb muscle function. MATERIALS AND METHODS: This study included 20 male subjects to perform the isokinetic muscle tests and the Wingate anaerobic power test on both knee joints under five closed-mouth conditions: without or with 4 types of mouthguards with thickness of 2 mm based on premolar area: (1) full-coverage, (2) anterior partial-coverage, (3) right posterior partial-coverage, and (4) left posterior partial-coverage. The obtained results were subjected to One-way ANOVA with repeated measures, followed by post hoc test of the contrast method (α=.05). RESULTS: There was no significant difference between the closed position with and without a full-coverage mouthguard in all variables. However, significant differences were observed between with and without a partial-coverage mouthguard in muscular endurance during extension of the left knee, muscular power and endurance during flexion of the right knee. Additionally, significant differences were found between occlusal states with full- and partial-coverage mouthguards in muscular power and endurance during extension of the left knee. CONCLUSION: These findings indicate the elevation of vertical dimension by 2 mm or the inducement of occlusal stability had little effect on isokinetic muscle strength and anaerobic performance, while uneven distribution of occlusal force might have some positive effects.